The study on the role of dedicators on promoting cooperation in public goods game. - Zhenghong Wu (Public Library of Science (PLoS), 2021)
In daily life, some people are always seen dedicating available resources to support collective activities. In this paper, we call these people who care group goals more than individual goals dedicators. Inspired by this phenomenon, we studied the role of dedicators on the evolution of cooperation in public goods game (PGG) based on a Chinese Folk Spring Festival Gala. Three types of agents were introduced into our PGG model including cooperators, defectors and dedicators. Dedicators tried to donate when the Gala was short of funds. Cooperators and defectors imitated the strategy of the highest-payoff neighbor based on the rational mechanism. And their imitating probability was modified on account of the emotional mechanism for positive effect of the dedicator's donating behavior and negative effect of continuous poor performance. Through numerical simulations, we found that the existence of dedicators can indeed promote cooperation in PGG. It should be noted that dedicators' willingness to donate was more important than their donation quantity in facilitating cooperation. And the stronger the emotional effect intensity of dedicators' donating behavior was, the better. So, the selfless dedication of participants should be praised to promote cooperation by improving their emotional effect intensity. Last but not least, a reasonable activity budget was needed to sustain the highest level of cooperation.